The Use of Interactive Teaching Methods in the Professional Military Training of Future Reserve Officers in Higher Education Institutions - Shemchuk, Vadym; Anishchenko, Viktoriia; Pentsak, Pavlo; Vakal, Andrii; Musiichuk , Volodymyr (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: The article examines improving professional military training for future reserve officers in higher education through interactive teaching methods. It analyzes their use across courses, evaluates effectiveness from students’ perspectives, and identifies organizational, content, and resource barriers. Particular attention is given to instructional design, emphasizing learner engagement, decision-making, feedback quality, and learning outcomes supported by digital simulations within contemporary technology-enhanced educational environments. Methodology: The study employed regulatory document analysis, classroom observation, and an empirical survey conducted at the Department of Military Training of Ivan Chernyakhovsky National Defence University of Ukraine. The sample included 92 respondents, comprising 44 teachers and 48 students. Main Findings: The results show that only 43% of classes applied interactive methods, while most relied on traditional lectures. Situational modelling (83%) and role-playing (71%) were most frequently used and rated highly effective by students. In contrast, multimedia simulations and self-management methods were least applied due to technical and methodological limitations. Key barriers included limited preparation time, restricted digital access, formalized assessment, and insufficient readiness. Findings reveal a gap between method frequency and learning impact, with simulation-based approaches most effective for developing flexible thinking, teamwork, cognitive load regulation, and situational adaptability. Novelty of this study: The study provides a systematic analysis of interactive training practices in Ukrainian military education focused on reserve officer preparation. It contributes to understanding how interactive and simulation-supported methods can enhance instructional design and offers practical recommendations for course restructuring, methodological support, and institutional development.